2016
DOI: 10.1136/vetreco-2016-000198
|View full text |Cite
|
Sign up to set email alerts
|

Canine parvovirus (CPV‐2) variants circulating in Nigerian dogs

Abstract: Canine parvovirus type 2 (CPV-2) is a highly contagious viral disease with three variants (CPV-2a, CPV-2b and CPV-2c) currently circulating in dogs worldwide. The main aim of this study was to determine the prevalent CPV-2 variant in faecal samples from 53 dogs presenting with acute gastroenteritis suspected to be and consistent with CPV-2 to Nigerian Veterinary Clinics in 2013–2014. Seventy-five per cent of these dogs tested positive for CPV-2 in a commercial antigen test and/or by PCR. Partial sequencing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
1
14
1
Order By: Relevance
“…Differently, since 2014 the analysed circulating CPV strains showed a closer connection with CPV strains of Asian origin. Despite some previously analysed CPV sequences lack of informative VP2 aa residues (5, 267, 324, 370), the comparison with our sequences suggested that both CPV‐2a and CPV‐2c strains collected in Nigeria after 2014 have a different phylogenetic origin with respect to previous analyses (Apaa et al, ; Fagbohun & Omobowale, ), suggesting a most recent introduction and spreading.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…Differently, since 2014 the analysed circulating CPV strains showed a closer connection with CPV strains of Asian origin. Despite some previously analysed CPV sequences lack of informative VP2 aa residues (5, 267, 324, 370), the comparison with our sequences suggested that both CPV‐2a and CPV‐2c strains collected in Nigeria after 2014 have a different phylogenetic origin with respect to previous analyses (Apaa et al, ; Fagbohun & Omobowale, ), suggesting a most recent introduction and spreading.…”
Section: Discussioncontrasting
confidence: 79%
“…Compared to CPV sequences previously analysed in Nigeria, the VP2 sequences of the analysed CPV‐2a strains showed 99.60%–99.25% (calculated on 1,750 nts), 99.87% (on 787 nts) and 99.34%–98.72% (on 459 and 470 nts) nt identities with strains collected in 2010, 2014 and 2017 (Apaa et al, ; Dogonyaro et al, ; Fagbohun & Omobowale, ), respectively. Compared to the CPV‐2a strains collected in 2010, three non‐synonymous changes (F267Y, Y324I and T440A) were observed (Table ).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…CPV-2 is a common etiological agent that causes severe gastroenteritis in puppies. The virus has a high detection rate in clinical samples, and the most characteristic signs of this illness are diarrhea, emesis, and anorexia (Apaa et al, 2016). Multiple studies have confirmed that CPV-2 coinfects with more than one enteric pathogen, including Canine enteric coronavirus, Canine circovirus (CanineCV), and Canine distemper virus (Costa et al, 2014;Kotsias et al, 2019;Navarro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%